Empathy is hard work: People choose to avoid empathy because of its cognitive costs - Cameron, C Daryl; Hutcherson, Cendri A; Ferguson, Amanda M; Scheffer, Julian A; Hadjiandreou, Eliana; Inzlicht, Michael (Journal of experimental psychology. General, 2019)
Empathy is considered a virtue, yet it fails in many situations, leading to a basic question: When given a choice, do people avoid empathy? And if so, why? Whereas past work has focused on material and emotional costs of empathy, here, we examined whether people experience empathy as cognitively taxing and costly, leading them to avoid it. We developed the empathy selection task, which uses free choices to assess the desire to empathize. Participants make a series of binary choices, selecting situations that lead them to engage in empathy or an alternative course of action. In each of 11 studies ( = 1,204) and a meta-analysis, we found a robust preference to avoid empathy, which was associated with perceptions of empathy as more effortful and aversive and less efficacious. Experimentally increasing empathy efficacy eliminated empathy avoidance, suggesting that cognitive costs directly cause empathy choice. When given the choice to share others' feelings, people act as if it is not worth the effort. (PsycINFO Database Record (c) 2019 APA, all rights reserved).